Host size and parasite density impact on the efficacy and reproductive output of Pyemotes zhonghuajia, a biological control agent of potato tuber moth - Xiao C; He XZ; Li X; Fan D; Zhang L; Wu C; Yang M; Hu J; Smagghe G; Liu J; Xu F (Springer Nature Switzerland AG, 2026)
The potato tuber moth (PTM), Phthorimaea operculella (Zeller), is a globally significant pest that attacks potatoes and many other Solanaceous crops. The ectoparasitic mite Pyemotes zhonghuajia Yu, Zhang & He is a promising biological control agent for PTM. This study investigated the effects of PTM larval body size (small and large) and P. zhonghuajia density (50, 150, and 250 mites) on host paralysis, as well as on the development and reproduction of P. zhonghuajia, aiming to optimize its mass production and application in PTM management. Our results showed that P. zhonghuajia females took significantly longer to paralyze and kill large PTM larvae at the lowest density (50 mites). Increasing mite density significantly decreased the parasitism rate per host, likely due to increased mutual interference among host-searching mites. However, the number of P. zhonghuajia females feeding on a single host increased significantly with mite density, resulting in smaller opisthosoma and fewer offsprings, suggesting food competition among females. Host size had a significant positive effect on opisthosoma size, offspring number per opisthosoma, and total offspring produced by P. zhonghuajia female, indicating that larger hosts provide more nutrients. The total number of offspring produced by P. zhonghuajia females from a host of a given size was similar across mite densities, suggesting that an optimal ratio of 50 P. zhonghuajia females per PTM larva is recommended for laboratory mass rearing and field augmentative release. Similar content being viewed by others